Local time in Lagrangian mechanics - Torres del Castillo, Gerardo Francisco (Revista Mexicana de Física E, 2022)
We show that under the replacement of the time by a local time in the Lagrange equations, the form of the equations is maintained if the Lagrangian does not depend explicitly on the time. We also study the corresponding modifications in the Hamilton equations and in the Hamilton–Jacobi equation.